Foreign direct invesment and perceptions of vulnerability to foreign exchange crises: Evidence from transition economies - Josef C. Brada; Vladimír Tomsik (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
We show that the imputation of reinvested profits of the subsidiaries of foreign firms as a debit item on a host country's balance of payments account tends to overstate the current account deficit and to make the host country seem more vulnerable to financial crisis. We also show that, because of the workings of the FDI financial life cycle, this phenomenon is most evident for countries that have recently received large inflows of capital. The transition economies of East Europe certainly fall among such countries, and we show that, for the Czech Republic and Hungary, this imputation has a large effect on their reported current account balance. We verify the working of the FDI financial life cycle using a panel of transition economies.
Keywords: F21; F23; F34; 330; balance of payments; foreign exchange crisis; foreign direct investment; transition economies